From Nicaea to Africa: Legacy, Inspiration, and Cultural Contextualization of Theology - Orobator, Agbonkhianmeghe E. ca. 1967 (2025)
This article explores the connection between the Council of Nicaea and the church in Africa through two main perspectives: geography and the contributions of African theologians as well as theological and christological developments. The first part highlights Africa’s geographical and cultural significance to Nicaea, examining the involvement of African theologians in the council’s outcomes. The second, more detailed section analyzes how themes rooted in Nicaea have continued to influence African Christianity even as modern theological discussions do not explicitly and consistently reference the council. Taken together, these sections trace the enduring impact of Nicaea on the evolution of African theological thought.
Keywords: Trinity; Orthodoxy; Nicene Creed; Jesus Christ; Culture; Council of Nicaea; Constantine; Community; African Christology; Athanasius; Arius; Alexander; African Theology